DO FIRM CHARACTERISTICS AFFECT TAX AVOIDANCE? A SENSITIVITY ANALYSIS - Herianti, Eva; Marundha, Amor; Haryanto, Haryanto (Universitas Kristen Krida Wacana, 2025)
This study examines the effect of firm characteristics on tax avoidance using an empirical approach. The research utilizes a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, selected through purposive sampling, resulting in 305 firm-year observations. The study employs multiple regression analysis and sensitivity testing to ensure robustness. The findings reveal that firm size and sales growth have no significant effect on tax avoidance, while profitability has a negative and significant effect. This suggests that firms with higher profitability are less likely to engage in tax avoidance practices. The study contributes to the literature by providing empirical evidence on the role of firm characteristics in tax strategies. It offers practical insights for policymakers and regulators in designing effective tax compliance policies. The results of the profitability sensitivity test on tax avoidance proxied from GAAP ETR to Cash ETR support the main test results, indicating that the findings of this study are robust and independent of the proxy used. Keywords: firm characteristics, tax avoidance, profitability, firm size, sales growth.